2005
DOI: 10.1007/s00467-005-2052-0
|View full text |Cite
|
Sign up to set email alerts
|

Strict cysteamine dose regimen is required to prevent nocturnal cystine accumulation in cystinosis

Abstract: Cystinosis is an autosomal recessive disorder, caused by mutations in the lysosomal cystine carrier cystinosin, encoded by the CTNS gene. The disease generally manifests with Fanconi syndrome during the first year of life and progresses towards end stage renal disease before the age of 10 years. Cysteamine depletes intralysosomal cystine content, postpones the deterioration of renal function and the occurrence of extra-renal organ damage. Based on the pharmacokinetic data, patients with cystinosis are advised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 16 publications
1
57
0
1
Order By: Relevance
“…Cystagon, approved in 1994 in the United States and 1997 in the European Union, requires a strict Q6H dosing schedule, including a midnight (or middle of the night) dose, and has significant side effects (29)(30)(31)(32), resulting in poor adherence in up to 70%-80% of patients (14). In the RP103 arm of the crossover study, patients were able to tolerate higher total single doses twice a day without using concomitant PPIs and to maintain an effective treatment regimen with no sleep interruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystagon, approved in 1994 in the United States and 1997 in the European Union, requires a strict Q6H dosing schedule, including a midnight (or middle of the night) dose, and has significant side effects (29)(30)(31)(32), resulting in poor adherence in up to 70%-80% of patients (14). In the RP103 arm of the crossover study, patients were able to tolerate higher total single doses twice a day without using concomitant PPIs and to maintain an effective treatment regimen with no sleep interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Because Cystagon must be taken every 6 hours (Q6H) around the clock based on the pharmacoefficiency of cystine depletion, patients must be awakened in the middle of the night to be fully adherent. One study demonstrated that ,25% of patients (5 of 22) were actually adhering to this regimen (14). There is evidence that failure to adhere to this strict Q6H dosing regimen results in more rapid deterioration of kidney function as WBC cystine levels rise (13).…”
Section: Introductionmentioning
confidence: 99%
“…These results are rather disappointing compared with the vast improvements expected from the pioneering studies (6,7). The observed difference can be attributed to less adequate treatment of NC patients on a large scale because of annoying side effects of the drug (24,25) and difficult dose regimen, leading to poor compliance (9). Furthermore, the rarity of NC might not allow physicians to have enough experience for the optimal monitoring of cysteamine treatment.…”
Section: Increased Age At Start Of Rrt In Nc Patientsmentioning
confidence: 97%
“…"Adequate" therapy includes an early diagnosis, thereby early initiation of cysteamine, possibly before 2 years of age, a strict 6-hour schedule, and regular monitoring of intraleukocyte cystine levels to adapt the daily dose (9). Patients who have been "adequately" treated have grown up to adulthood in recent years, allowing analysis of the effect of cysteamine treatment on renal outcome in NC.…”
Section: Introductionmentioning
confidence: 99%
“…The currently most widely used formulation of the drug is cysteamine bitartrate (trade name Cystagon®, Mylan Pharma, USA). The cystine depleting effect of the drug lasts no longer than 6 h, and the drug should be administered 4 times per day [2]. In 2007 it was demonstrated that cysteamine administration directly into the small intestine led to higher cysteamine plasma levels with higher area under the curve (AUC), compared to gastric administration [3].…”
Section: Introductionmentioning
confidence: 99%